Globalisation at the crossroad: an “International Panel on Systemic Risks in the Global Economy” is needed - Dirk Messner; Enrique Saravia; Elisabeth Sidiropoulos; Yizhou Wang (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
The global economic crisis creates the chance to build a more stable, sustainable and fair global economic governance structure. The financial as well as the climate crisis demonstrate that human ankind is confronted with a growing number of global systemic risks. Guided by the experience gained with the “International Panel on Climate Change” (IPCC), we advocate for the establishment of a standing International Panel on Systemic Risks in the Global Economy and outline possible tasks for this international network of researchers in support of global governance processes.
Keywords: 330